2004
DOI: 10.1197/j.aem.2003.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Household Addresses That Repeatedly Contact 911 to Report Intimate Partner Violence

Abstract: Ethnic differences in 911 use for IPV exist between African Americans, whites, and Hispanics. However, unknown societal, economic, or cultural issues could have influenced this finding. Households that repeatedly contacted 911 during the study interval to report IPV were not more likely to experience severe violence than those that placed a single 911 call.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
(16 reference statements)
0
11
1
Order By: Relevance
“…For example, it is possible that police underestimated the violence that occurred. Second, our use of police data likely overrepresented severe abuse cases (Bonomi, Holt, et al, 2006;Duterte et al, 2008;Houry et al, 2004). Third, it is possible we missed subsequent intimate partner violence not reported to police; for example, we could not determine whether women migrated differentially out of neighborhood areas, which may have influenced data capture rates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible that police underestimated the violence that occurred. Second, our use of police data likely overrepresented severe abuse cases (Bonomi, Holt, et al, 2006;Duterte et al, 2008;Houry et al, 2004). Third, it is possible we missed subsequent intimate partner violence not reported to police; for example, we could not determine whether women migrated differentially out of neighborhood areas, which may have influenced data capture rates.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of police-reported IPV is rarely reported beyond self-report survey data. Houry et al (2004), using 911 phone logs, used key phrases corresponding to each CTS score to identify IPV cases and score the severity of the incidents. Although that study revealed a preponderance (87%) of severe IPV, the specific charges against the perpetrator were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of IPV in the state courts of 16 large urban counties, Smith and Farole (2009) found that 81% of male perpetrators were charged with simple assault, a misdemeanor. A few studies supplementing qualitative with quantitative data have demonstrated a substantial level of severe IPV in police-reported incidents (Houry et al, 2004; Thomas et al, 2010); at least one (Thomas et al, 2010) found police charges and actual behaviors encountered in incidents to be discordant, with the majority of incidents classified as severe physical violence using narrative text whereas the majority of charges were simple assault.…”
Section: Introductionmentioning
confidence: 99%
“…In some locales, the numbers may be so high as to comprise more than one half of all calls for service (Klein 2009). Given that so many IPV victims seek help from the police (Friday et al 2006;Hutchison and Hirschel 1998), and that many do so repeatedly (Friday et al 2006;Houry et al 2004), it is important that agencies focus and dedicate as much time and resources to IPV as they do to other major crimes (Klein 2009). Similar to findings from previous research and what experienced police officers have learned, we found that a majority of IPV incidents occurred between the evening and early morning hours (Catalano 2006;Johnson 2007), on weekends (Johnson 2007;Shepherd 1990), and on major American holidays (Rotten and Frey 1985).…”
Section: Discussionmentioning
confidence: 99%